2010
DOI: 10.1292/jvms.09-0487
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin E on the Osteoblast Differentiation

Abstract: ABSTRACT. Vitamin E is thought to affect bone formation and bone remodeling. In this study, we investigated the effects of vitamin E (-tocopherol and -tocopherol) on the osteoblasts isolated from rat calvariae. At 4 and 7 days (Day 4 and 7) after induction of osteoblastic differentiation, treatment of -tocopherol (100 and 200 M) and -tocopherol (2 and 20 M) for 3 days significantly decreased alkaline phophatase activity of the cultured osteoblasts. At Day 14, however, no significant change was detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 37 publications
2
25
0
4
Order By: Relevance
“…(77,79) A recent in vitro study showed that alpha-tocopherol inhibited differentiation of osteoblasts. (80) Given that BAP reflects the differentiation stage of osteoblastogenesis, (81) it is possible that excess alphatocopherol intake may reduce BAP levels. Although we found significant inverse associations between total alpha-tocopherol intake and serum alpha-tocopherol and BAP levels in the unadjusted analysis, these relationships disappeared after adjusting for confounders.…”
Section: Discussionmentioning
confidence: 99%
“…(77,79) A recent in vitro study showed that alpha-tocopherol inhibited differentiation of osteoblasts. (80) Given that BAP reflects the differentiation stage of osteoblastogenesis, (81) it is possible that excess alphatocopherol intake may reduce BAP levels. Although we found significant inverse associations between total alpha-tocopherol intake and serum alpha-tocopherol and BAP levels in the unadjusted analysis, these relationships disappeared after adjusting for confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Soeta et al [5] suggested alpha-and delta-tocopherol inhibited the differentiation of osteoblasts, especially from early stage to osteoid-producing stage in cultures of osteoblasts isolated from rat calvariae. An interesting finding on the dose-dependent paradoxical effect of gamma-tocopherol on osteoblasts cell culture was described by Abd Manan et al [6]: low doses (1 and 10 M) protected osteoblasts against H2O2-induced oxidative stress and apoptosis; however, high doses (100 M) reduced glutathione peroxidase activity and promoted apoptosis.…”
Section: Vitamin E and Bone Healthmentioning
confidence: 99%
“…Soeta ve ark. 46 tarafından yapılan çalışmada δ-tokoferol ve α-tokoferol'ün osteoblast farklılaşması üzerinde etkili olduğu bildirilmiştir. İlk yedi günlük dönemde α-tokoferol ve δ-tokoferol uygulamasıyla alkalen fosfataz aktivitesinin ve kalsifiye olmamış nodül sayısının azaldığı rapor edilmiştir.…”
Section: Gereç Ve Yöntemunclassified
“…Vitamin E uygulamasının osteoblast farklılaşmasını osteoid üretiminin erken fazında etkilediği belirtilmiştir. 46 Periodontal doku yıkımında tedaviye yardımcı olarak E vitamini uygulanmasına yönelik çalışmalar sınırlı sayıdadır. 21,47 Sıçanlara diyetle birlikte verilen E vitaminin üç ay sonunda AKK üzerine etkili olmadığı, ancak rotasyonel strese bağlı oluşan kemik yıkımına yatkın bölgelerde E vitamini uygulamasının koruyucu bir etki sağlayabileceği belirtilmiştir.…”
Section: Gereç Ve Yöntemunclassified